Navigating faith: Crafting effective strategies for engaging generation z in religious character formation - Furqoni, Ridwan; Shodiq, Sadam Fajar; Nur Ilfi Aisah (Yayasan Azhar Amanaa Yogyakarta, 2024)
Generation Z, having come of age in a thriving and varied digital age, encounters distinct obstacles in cultivating their religious identity. This article explores the most effective ways for engaging Generation Z in religious character building and examines the resulting ramifications. The methodology employed is qualitative, with descriptive analysis as the study type. The research focused on the following subjects: the madrasah's head, the curriculum section, male and female student affairs, and the students. Data gathering approaches employ methods such as interviews, documentation, and observation. Data analysis techniques encompass various stages, namely data collecting, data reduction, data display, and drawing conclusions. Studies indicate that the utilization of digital technology, including social media and educational applications, can effectively transmit religious ideals to Generation Z. Furthermore, the implementation of a comprehensive strategy that encompasses both structured and unstructured learning, interpersonal engagement, and guidance from mentors has also demonstrated its efficacy. The significance of these findings underscores the necessity of adapting religious learning methodologies to cater to the requirements and inclinations of Generation Z. This essay emphasizes the necessity of using creative approaches to engage Generation Z in the development of religious character, with the aim of preserving spiritual values in the rapidly changing modern world.